1971
DOI: 10.1071/ar9710383
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of leaf scald of barley

Abstract: Studies on the spread of leaf scald of barley from an infection focus showed that infected straw was the source of primary inoculum. The disease progressed mainly between adjacent plants but pockets of infection appeared in the crop at isolated positions several metres away from the source of inoculum. Sporulation occurred when free water was available and the conidia were trapped simultaneously with rainfall or irrigation. Some conidia were caught under windy but rainless conditions. Conidia were trapped at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Mildew, brown rust and yellow rust can be wind-spread over considerable distances and this would tend to obscure any correlation with previous cropping, whilst net blotch is primarily seed-transmitted, although it can also be carried over on stubble debris. Spread of infection is probably mainly local in the case of leaf blotch (Evans, 1969;Ayesu-Offei and Carter, 1971) and halo spot, and it might be expected that these diseases would be more severe following previous cropping with barley. The survey gave some indication of this effect but it was not statistically significant.…”
Section: Effect Of Previous Cropping On Diseasementioning
confidence: 99%
“…Mildew, brown rust and yellow rust can be wind-spread over considerable distances and this would tend to obscure any correlation with previous cropping, whilst net blotch is primarily seed-transmitted, although it can also be carried over on stubble debris. Spread of infection is probably mainly local in the case of leaf blotch (Evans, 1969;Ayesu-Offei and Carter, 1971) and halo spot, and it might be expected that these diseases would be more severe following previous cropping with barley. The survey gave some indication of this effect but it was not statistically significant.…”
Section: Effect Of Previous Cropping On Diseasementioning
confidence: 99%
“…The pathogen is expected to move mainly over short distances because asexual spores (conidia) are dispersed by rain‐splash, therefore the dispersal of clones is expected to be restricted to within a field or to nearby barley fields (e.g. Ayesu‐Offei & Carter 1971). Long‐distance dispersal is thought to occur by the movement of infected seed and small windblown pieces of infected material (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have reported that the most important factors influencing the disease progress curve are temperature and leaf wetness (Ayesu-Offei & Carter, 1971;Fowler & Owcn, 1971;Polley, 1971;Ryan & Clare, 1975;Stedman, 1980;Pietsch, 1984). Different authors have reported that the most important factors influencing the disease progress curve are temperature and leaf wetness (Ayesu-Offei & Carter, 1971;Fowler & Owcn, 1971;Polley, 1971;Ryan & Clare, 1975;Stedman, 1980;Pietsch, 1984).…”
Section: Parameters Affecting Biology and Epidemiology Of Rh Ynchospomentioning
confidence: 99%